Kepemilikan Manajerial, Kepemilikan Institusional, Komisaris Independen, Komite Audit, dan Nilai Perusahaan - Bakhtiar, Hafidz Andra; Nurlaela, Siti; Hendra, Kartika (AFRE (Accounting and Financial Review), 2021)
Competition between companies is getting tougher and more competitive because the cor-porate world is growing rapidly. Every company wants high company value, a company with high company value can increase shareholder prosperity. If the shareholders feel pros-perous, then the shareholders may be able to add value to their investment in the company. Good corporate governance (GCG) is one of the many factors that can affect corporate value. The purpose of this study was to examine the effect managerial ownership, institu-tional ownership, independent commissioners, and audit committees on firm value. The population used as the object of this research is the banking sub-sector listed on the Indone-sia Stock Exchange (IDX) in 2014-2018. The population of this study is 43 companies, this study was obtained by purposive sampling technique which then produced a sample of 25 companies the financial sector banking sub sector to be studied. The analysis technique used is multiple linear regression analysis. Based on data analysis and discussion it can be concluded that Managerial Ownership and Independent Commissioners do not affect the company’s value. While the Institutional Ownership and Audit Committee affect the value of the company. DOI: https://doi.org/10.26905/afr.v3i2.3927